Effect of core-to-shell flowrate ratio on morphology, crystallinity, mechanical properties and wettability of poly(lactic acid) fibers prepared via modified coaxial electrospinning. (10th December 2021) - Abdullah, Muhammad Faiq; Andriyana, Andri; Muhamad, Farina; Ang, Bee Chin
Abstract: In this study, modified coaxial electrospinning (CE) was employed to improve electrospinnability and to tailor surface morphology and bead formation of poly(lactic acid) (PLA) fibers by means of core-to-shell flowrate ratio variation. Chloroform/N, N-dimethylformamide (DMF) mixture was used as sheath solution which serves as a protective layer to prevent rapid solidification of PLA droplet causing needle clogging. Five different core-to-shell flowrate ratios yielded beads-on-a-string PLA fibers with distinctive fiber and bead properties. These diverse morphologies were characterized in terms of fiber diameter (Df ), fiber percentage (Pf ), number of beads per area (nb ), bead area (Ab ), bead aspect ratio (Lb /Db ), ratio of bead-to-fiber diameter (Db /Df ) and surface roughness. From thermal analysis, crystallinity of PLA fibers was shown to be significantly dependent on the fiber processing history, where higher degree of molecular chain orientation and longer jet flight time correspond to higher crystallinity values. Core-to-shell flowrate ratio of 1:3 resulted in PLA fibers with the least nb, smallest Db /Df and highest Lb /Db (spindle-like shape), which correspond to the highest tensile properties and minimum hydrophobicity among beads-on-a-string fibers studied, as indicated by effective stress-strain curve and water contact angle measurement. Furthermore, the results suggested that Db /Df was the dominant factor affecting tensile properties more than the effect of crystallinity, while Lb /Db (bead shape) was the key aspect which influenced the wettability of the PLA beads-on-a-string fibers. Graphical abstract: Image 1 Highlights: Clogging was eliminated through employment of modified coaxial electrospinning. Core-to-shell flowrate ratio variation yielded distinctive fiber/bead properties. Tensile properties were predominantly affected by bead-to-fiber diameter ratio. Bead aspect ratio primarily influencing the wettability of beads-on-a-string fibers.